THE DEVELOPMENT OF AN OPEN ONLINE LEARNING RESOURCE ON MARKETING MIX FOR HIGHER VOCATIONAL CERTIFICATE STUDENTS AT LUANG PRATHAN RATNIKORN INDUSTRIAL AND COMMUNITY EDUCATION COLLEGE - Asawimolkit, Boosya; Luangrangsee, Pol (Journal of MCU Nakhondhat, 2025)
This research aims to develop an open online learning resource to enhance learning achievement on the marketing mix based on the 80/80 criterion, compare trends in learning achievement on the topic, and assess student satisfaction with the resource. The study follows a research and development (R&D) methodology, with a sample of Higher Vocational Certificate students in the Marketing Department at Luang Prathan Ratnikorn Vocational College, Hat Yai, Songkhla, in the second semester of the 2024 academic year, selected through purposive sampling. The research instruments included the open online learning resource, rated as highly appropriate (mean = 4.53) and highly accurate (mean = 4.80); a learning achievement test, with an item-objective congruence index ranging from 0.67 to 1.00 and a reliability coefficient of 0.81; and a satisfaction questionnaire, with an item-objective congruence index ranging from 0.67 to 1.00 and a reliability coefficient of 0.85. Data analysis used mean, standard deviation, and tracking measurement with the Friedman test. The findings revealed that the open online learning resource, consisting of a homepage, registration page, login page, welcome page, course enrollment page, lesson page, certificate page, and course creator page, had an efficiency score of 81.68/80.73; the trend in learning achievement on the marketing mix significantly increased at the .05 level; and student satisfaction with the resource was high ( = 4.47, S.D. = 0.49).